Risk factors for poor prognosis in patients with zoster-associated neuralgia who underwent interventional pain management - Yuan, Junpeng; Yu, Youjia; Liu, Hong; Xu, Huichan; Li, Yan; Jin, Xiaohong (Frontiers in Molecular Neuroscience, 2024)
BackgroundZoster-associated neuralgia (ZAN) is recognized as a challenging neuralgia that often leads to poor prognosis in patients receiving interventional pain management. Identifying risk factors early can enable clinicians to develop personalized treatment plans; however, research in this area is limited.MethodsWe retrospectively screened all patients with ZAN who received interventional therapy in the Pain Department of Soochow University First Affiliated Hospital from January 1, 2022 to August 31, 2023. Data on patient demographics, medical history, neutrophil-to-lymphocyte ratio (NLR), clinical scoring, and treatment methods were collected. Interventional therapy included short-term nerve electrical stimulation (st-NES), pulsed radiofrequency (PRF) and radiofrequency thermocoagulation (RF-TC). Patients were categorized into poor prognosis and control groups based on outcomes 3 months post-discharge. Multivariate logistic regression was used to identify risk factors for poor prognosis.ResultsThe final analysis included 282 patients. The rate of poor prognosis was 32.6% (92/282). Multivariate logistic regression analysis revealed that age ≥ 65 years (odds ratio, 2.985; 95% confidence interval, 1.449–6.148; p = 0.003), disease duration >3 months (odds ratio, 3.135; 95% confidence interval, 1.685–5.832; p < 0.001), head and face pain (odds ratio, 3.140; 95% confidence interval, 1.557–6.330; p = 0.001), use of immunosuppressants (odds ratio, 2.737; 95% confidence interval, 1.168–6.416; p = 0.021), higher NLR (odds ratio, 1.454; 95% confidence interval, 1.233–1.715; p < 0.001), PRF (st-NES as reference) (odds ratio, 2.324; 95% confidence interval, 1.116–4.844; p = 0.024) and RF-TC (st-NES as reference) (odds ratio, 5.028; 95% confidence interval, 2.139–11.820; p < 0.001) were found to be independent risk factors for poor prognosis in patients with ZAN who underwent interventional pain management.ConclusionAge ≥ 65 years (odds ratio, 2.985; 95% confidence interval, 1.449–6.148; p = 0.003), disease duration >3 months (odds ratio, 3.135; 95% confidence interval, 1.685–5.832; p < 0.001), head and face pain (odds ratio, 3.140; 95% confidence interval, 1.557–6.330; p = 0.001), immunosuppressants use (odds ratio, 2.737; 95% confidence interval, 1.168–6.416; p = 0.021), higher NLR (odds ratio, 1.454; 95% confidence interval, 1.233–1.715; p < 0.001), PRF (odds ratio, 2.324; 95% confidence interval, 1.116–4.844; p = 0.024) and RF-TC (odds ratio, 5.028; 95% confidence interval, 2.139–11.820; p < 0.001) were identified as independent risk factors for poor prognosis in patients with ZAN who underwent interventional pain management.